FriDatE: Pengembangan Potensi Kemampuan Debate Mahasiswa Tingkat Karesidenan Madiun - Nimasari, Elok Putri; Gestanti, Rohfin Andria (Universitas Muhammadiyah Surabaya, 2018)
Debate is a competence that must be owned by students because in addition to including a prestigious event, debate as a place for students to think critically (critical thinking) and convey the thought well and systematically. The willingness and ability of good students in debating should be a good quality asset of the young generation. However, their great motivation is hampered if there is no container that they can make a place to develop the skills they already have. FriDatE's community service activities,